Pengaruh Penjualan Langsung (Personal Selling) Produk Pakaian Seragam Sekolah Terhadap Minat Beli: Studi Pada Sejumlah Sales di CV Sadar Mandiri - Syarifuddin, Andi St Mawa. A (Prisani Cendekia Institute, 2023)
This study aims to determine there is an influence of personal selling on buying interest at CV Sadar Mandiri and how it influences. This study uses survey methode through questionnaires distributed to 100 respondents. The questionnaire in this study uses a differential semantic measurement scale with 9 scales. The questionnaire was tested by using a normalitas test, simple linear regression, correlation test, and determination test. The results of this study indicate that personal selling has a significant effect of 83% on Purchase Intention of CV Sadar Mandiri Consumers. Other results show that there is a very strong influence between personal selling and buying interest with a correlation rate of 91.1%.